L’orthopédagogie IFO en France : au carrefour de l’innovation et de la transformation collaborative des métiers de l’éducation - Dorothée Muraro (Questions Vives)
Emerging profession in France, IFO orthopedagogy asks at several levels the educational ecosystem as it exists today for a vulnerable learner. Practiced inside and outside the school walls, it privileges the “relate” between professionals to ensure pooling of their specific knowledge and know-how, the involvement of both parts and the global coherence. Limits like dead ends become open borders where complementary knowledge mingle with additional knowledge. From its legitimacy to its practice, including its relashionship with other specialists, it will therefore be question of wondering about the collective and innovative dimension of this new profession as it is developing at the French Institute of Orthopedagogy from professional experiences conducted since 2014 within schools and organizations.